3D Reconstruction of the Surface Using a Standard Camera. (29th November 2017) - Martišek, Dalibor
Abstract : This paper deals with 3 D reconstructions of series of partially focussed images. Some of these methods are known in case of images which were acquired in small field of view (by confocal microscope or CCD camera, e.g.). In this case, recorded images do not differ in any geometrical transformation from each other. In case of larger samples (oversized for microscope or CCD camera), it is necessary to use wider viewing field (standard cameras, e.g.), and taken images primarily differ in scaling but may also differ in shifting and rotation too. These images cannot be used for reconstruction directly; they must be registered; that is, we must determine all transformations which the images differ and eliminate their effects. There are several ways to do this. This paper deals with the registration based on phase correlation. After this registration, it is necessary to identify the sharp parts and to compose a 2 D and 3 D model. Present methods are very sensitive to noise and their results are not satisfactory in many cases. We introduce a new method for 3 D reconstruction which is significantly better.